Neuregulin, an Effector on Mitochondria Metabolism That Preserves Insulin Sensitivity - Gumà, Anna; Díaz-Sáez, Francisco; Camps, Marta; Zorzano, Antonio (Frontiers in Physiology, 2020)
Various external factors modulate the metabolic efficiency of mitochondria. This review focuses on the impact of the growth factor neuregulin and its ErbB receptors on mitochondria and their relationship with several physiopathological alterations. Neuregulin is involved in the differentiation of heart, skeletal muscle, and the neuronal system, among others; and its deficiency is deleterious for the health. Information gathered over the last two decades suggests that neuregulin plays a key role in regulating the mitochondrial oxidative machinery, which sustains cell survival and insulin sensitivity.